Pt–calcium cobaltate enables sorption‐enhanced steam reforming of glycerol coupled with chemical‐looping CH4 combustion. Issue 11 (4th August 2021) - Li, Hanke; Dang, Chengxiong; Li, Yuhang; Yang, Guangxing; Cao, Yonghai; Wang, Hongjuan; Peng, Feng; Yu, Hao
Abstract: Sorption‐enhanced steam reforming (SESR) process is usually highly energy intensive in producing high‐purity hydrogen. Herein, the sorbent decarbonation was conducted in the presence of O2 to enable the exothermic reaction between CaO and CoO x to form calcium cobaltate (CCO). By utilizing CCO as oxygen carrier (OC), the chemical‐looping methane combustion was employed prior to the SESR of glycerol (SESRG), by which CCO was prereduced to Co catalysts and CaO sorbent, thereby significantly improving the H2 yield from SESRG. With a Pt‐doped CCO acting as precatalyst, CO2 sorbent, and OC, we realized 70% CH4 conversion and 96 vol% H2 with 120% yield (based on glycerol) for 20 cycles, and the excess H2 was due to steam gasification of coke. The promoting effects of Pt toward CH4 conversion and H2 production were rationalized by CH4 temperature‐programmed reduction, X‐ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy. Our results demonstrate the feasibility of process integration enabled by multifunctional materials.